Contracts with Professional Athletes - Csicsay, Peter (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
The theme of the work is contractual relations with professional athletes in sports law. The article first attempts to define athletes from a legal standpoint. It then proceeds to analyze the various types of contracts that professional athletes engaged in sports activity might conclude when viewed through the prism of the Slovakia Labor Code, the Commercial Code and the Sports Act. It then explores how contracts in connection with the professional performance of sport are impacted by other regulations, both transnational and national. Special attention is given to the analysis of contractual provisions dealing with the termination of the contract on the professional performance of sports, both from the owner’s and club’s perspective and that of the athlete. Special emphasis is placed on analyzing moral clauses in such contracts as a legitimate reason for terminating the contract.